THE INFLUENCE OF PRODUCT EXPERIENCE AND FOOD COOKING HABIT ON COVID-19 TOWARDS REPURCHASE READY-MADE FROZEN FOOD - Felix Goenadhi (Proceeding of the International Conference on Family Business and Entrepreneurship, 2021)
The Covid-19 is forced the worker to work from home, self-isolation, or any other condition that makes them should be at their home, however, they need to eat, and workers usually purchases a meal from a restaurant, canteen, or any other ready to eat suppliers. Thisresearch focuses on repurchase ready-made frozen food based on product experience, that containsthe aesthetic experience, experience meaning, and emotional experience, and food cooking habit on Covid-19 pandemic. The research aim is to see the need from customers and the result is for ready-made frozen food from homemade suppliers to giving a business strategy. This research using SPSS ver. 20 and the result from 350 respondents, isthe aesthetic experience is not giving a significant to repurchase ready-made frozen food, however, the food cooking habit on Covid19 in increasing, and the experience meaning is giving the highest contribution in repurchase ready-made frozen food. The strategy of supplier ready-made frozen food is to have inline products and giving a nutrition value to the customers.Keywords: Product Experience, Food Cooking Habit, Ready-Made Frozen Food, Small Medium Enterprise